Nightmares and Dysfunctional Beliefs about Sleep Mediate the Effect of Insomnia Symptoms on Suicidal Ideation - McCall, W. Vaughn (American Academy of Sleep Medicine, 2013)
STUDY OBJECTIVES: Many studies have reported a positive association between sleep problems and suicidal ideation. Some prospective studies in the elderly have shown that insomnia is a risk factor for suicide death after controlling for other depressive symptoms. However, hypotheses to explain how this risk is mediated have not previously been assessed. We tested the hypothesis that insomnia symptoms are related to suicidal ideation through mediation by dysfunctional beliefs and attitudes about sleep and/or nightmares. METHODS: We measured symptoms of depression, hopelessness, insomnia severity, dysfunctional beliefs and attitudes about sleep, nightmares, and suicidal ideation intensity on a convenience sample of 50 patients with depressive disorders, including 23 outpatients, 16 inpatients, and 11 suicidal ED patients. Mediation analysis was used to assess the indirect effects of insomnia symptoms on suicidal ideation through dysfunctional beliefs about sleep and through nightmares. RESULTS: Our findings again confirmed a positive association between insomnia symptoms and the intensity of suicidal ideas in depressed patients (b = 0.64, 95% CI = [0.14, 1.15]). However, we extended and clarified our earlier findings by now showing that dysfunctional beliefs and attitudes about sleep as well as nightmares may mediate the association between insomnia symptoms and suicidal ideation. The indirect effects of insomnia symptoms through dysfunctional beliefs about sleep and through nightmares were 0.38 (-0.03, 0.97) and 0.35 (0.05, 0.75), respectively. CONCLUSIONS: Nightmares as well as dysfunctional beliefs and attitudes about sleep each are positively and independently related to the intensity of suicidal ideation, and the effect of insomnia symptoms appears to be mediated through these two variables. CITATION: McCall WV; Batson N; Webster M; Case LD; Joshi I; Derreberry T; McDonough A; Farris SR. Nightmares and dysfunctional beliefs about sleep mediate the effect of insomnia symptoms on suicidal ideation. J Clin Sleep Med 2013;9(2):135–140.